Implementasi Kegiatan Muhadharah dalam Meningkatkan Nilai-Nilai Keislaman di MTS Al Asyhar Sungonlegowo - Kharis Abdul Rozzaq; Moh. Syafi’i (KOLONI, 2026)
Theoretical Islamic Religious Education (PAI) in classrooms has limitations in fully internalizing Islamic character values in students. Muhadhoroh activities serve as an applicative, habit-based solution to train psychological state, communication skills, and plant religious values simultaneously. This study aims to describe the planning, implementation, and evaluation processes of muhadhoroh activities, and analyze its role in enhancing students' values of aqidah, ibadah, and akhlak at MTs Al Asyhar Sungonlegowo. A qualitative approach with a descriptive method is applied in this research. The primary subjects include the headmaster, supervising teachers, and students. Data are gathered through non-participant observation, semi-structured interviews, and documentation techniques. The data analysis utilizes an interactive model consisting of data reduction, data display, and conclusion drawing. The conceptual projection of this research proposal indicates that the transaction and trans-internalization stages of values within muhadhoroh are projected to foster discipline, responsibility, and strengthen students' Islamic character in daily life.